2018
DOI: 10.1038/s41598-018-32370-w
|View full text |Cite
|
Sign up to set email alerts
|

Brcal Defective Breast Cancer Cells Induce in vitro Transformation of Cancer Associated Fibroblasts (CAFs) to Metastasis Associated Fibroblasts (MAF)

Abstract: It is known that Cancer Associated Fibroblast (CAFs) from the primary tumor site can accompany cancer cells to a secondary site during the process of metastasis. We hypothesize that these CAFs could be transformed to an altered cell type, which can be called as Metastasis Associated Fibroblasts (MAF) in turn can support, and convoy cancer cells for metastasis. There are no published reports that have characterized and distinguished CAFs from MAF. It is well established that some of the cancer cells within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
1
9
0
1
Order By: Relevance
“…4 CAFs are essential components of TME. They play pivotal roles in tumor progression in various types of tumor, such as lung cancer, 5 breast cancer, 6 pancreatic cancer. 7 CAFs are involved in many physiological processes such as epithelial-mesenchymal transition (EMT), chemoresistance, matrix remodeling, metastasis and immunosuppression by secreting cytokines and growth factors and creating an optimal microenvironment for tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…4 CAFs are essential components of TME. They play pivotal roles in tumor progression in various types of tumor, such as lung cancer, 5 breast cancer, 6 pancreatic cancer. 7 CAFs are involved in many physiological processes such as epithelial-mesenchymal transition (EMT), chemoresistance, matrix remodeling, metastasis and immunosuppression by secreting cytokines and growth factors and creating an optimal microenvironment for tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Other study showed that BRCA1 -deficient breast cancer cells can transform CAFs to their altered activated phenotype, which the authors named metastasis associated fibroblasts (MAFs). MAFs can subsequently induce metastatic changes in the breast cancer cells and accompany them during metastasis [ 69 ]. It was previously shown that BRCA1 colocalizes with Ezrin, Moesin, Radixin and F-actin and controls cell motility [ 70 ].…”
Section: Brca1/2 -Deficient Tumor Microenvironmmentioning
confidence: 99%
“…It was previously shown that BRCA1 colocalizes with Ezrin, Moesin, Radixin and F-actin and controls cell motility [ 70 ]. In connection with this information, MAFs induce changes in proliferation, invasion and migration of cancer cells, which are linked to the elevated expression of EMT markers, Ezrin and CCL5 in these cells [ 69 ].…”
Section: Brca1/2 -Deficient Tumor Microenvironmmentioning
confidence: 99%
“…Interestingly, inhibition of Ezrin and CCL5 in MAFs reduces their capability to promote cancer cell migration and invasion in vitro. Therefore, Ezrin and CCL5 could represent promising targets to prevent the differentiation of BCAFs into a more metastatic phenotype, especially in BRCA1 mutated tumors [ 206 ]. A recent study demonstrated that pBCAFs and metastatic BCAFs (mBCAFs) isolated from skin, lung, liver, and bone metastases exhibit distinct gene expression profiles.…”
Section: Role Of Bcafs In Bc Cell Dissemination and Metastasismentioning
confidence: 99%